The Relationship Between Conformity and Brand Switching Intention on Adolescent Handphone Brand - Syarifah Fajriyah; Komarudin Komarudin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the relationship between conformity with brand switchingintentions of cellphone brands among adolescents in Sungailiat Bangka district. Thehypothesis in this study is that there is a positive relationship between conformity withbrand switching intentions of cellphone brands in adolescents. Subjects in this study were190 adolescents in Sungailiat Bangka sub-district, aged 16-21 years. The data collectionprocess in this study used two scales; they are conformity scale and brand switchingintention scale. The conformity scale consisted of 46 items while the brand switchingintention consisting of 45 items. The data analysis technique used the product-momentcorrelation technique to find out more about the relationship between the independentvariables, namely conformity and dependent variables, namely the intention of brandswitching. The researcher found that the calculation result of r ^ 2 was 0.999 with apercentage of 99.9% and a p-value of 0.000.